[Rezension von: Dalferth, Ingolf U., 1948-, Wirkendes Wort : Bibel, Schrift und Evangelium im Leben der Kirche und im Denken der Theologie] - Burger, Hans (European journal of theology, 2020)
In this book Ingolf Dalferth offers his thoughts on Scripture. His central thesis is that we have to distinguish between the Word of God, Scripture and the Bible. Protestantism fell into the trap of Gutenberg and turned into a movement of a printed book. Theology has to rediscover that the Word of God is not a printed book. Dalferth poses important questions to orthodox Protestant and evangelical theology. Indeed, Protestantism has identified Scripture with a book in a problematic way, but in Dalferth's alternative, the distinction between Word of God, Scripture and Bible, is too sharp.